Ethical issues in human population genetics - Greely, Henry (Henry Stewart Talks, 2007)
The ethical issues in human genetics, ELSI issues, DNA in establishing identity, DNA in unveiling the past, DNA predicts the future, Manipulation of DNA, Ownership and control of DNA, Deeper cultural changes, Population genetics, DNA in group history, The Navajo people, DNA in group stigma, DNA in exploitation, DNA and racism, DNA and biological warfare, The consent of a research population, The NIH alternative for consent, Control, Confidentiality, Return of information, Benefit sharing, Update interview: Large scale genomic databases: UK Biobank, All of Us, Update interview: Consumer genomics companies: Ancestry, 23andMe, Update interview: Government databases for forensic purposes: China, Uyghurs, Update interview: Electronic health/medical records, Update interview: Ancient DNA, Update interview: Indigenous peoples, Update interview: Privacy: Re-identification and De-identification, Update interview: Genetic genealogy, Update interview: Probabilistic Risk Scores
Updated at 2021/05/31